STRATEGI PEMBERANTASAN KORUPSI BIROKRASI MELALUI SISTEM JARINGAN ANTAR ORGANISASI DI INDONESIA - Alwi Alwi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2005)
Corruption represents a misconduct in bureaucratic administration. Generally, corruption occurs at either individual, organizational, or societal level. As stated in public administration and public management literatures, inter-organizational collaboration is needed to eradicate corruption practices because they are usually out of reach of institutions in charge of corruption abolition. Legal approach has so far been unable to combat the corruption practices because it only deals with a sequence of corruption cases as crimes against the law without,comprehending the underlying causes stimulating such deeds. Having known the intricacy of corruption practices, an independent state commission for corruption abolition (KPK) develops inter-organizational networks to comprehensively exterminate corruption.In order to abolish corruption, this state commission recommends several conditions, such as: a) effective and efficient use of sources, b) raised incentives for employees, c) recovery of the reputation of judicial institutions, and d) definite legitimacy of judicial institutions.